The Cytotoxicity of Endophytic Fungi Isolated from Kelakai (Stenochlaena palustris) Against MCF-7 and Vero Cells - Dali; Mashar, Harlyanti Muthma’innah; Damiti, Sukmawati Ahmad; Ysrafil, Ysrafil (YCAB Publisher, 2025)
Background: The high prevalence of cancer has a direct impact on the quality of life and nutritional status of sufferers, mainly due to decreased appetite, metabolic disorders, and side effects of conventional therapies such as surgery, mastectomy, chemotherapy, hormonal therapy, or radiation therapy. These therapies, although aimed at inhibiting the growth and metastasis of cancer cells, often cause severe side effects that worsen the patient's condition. Therefore, it is important to explore alternative treatments that are effective and have minimal side effects. In this regard, biological sources, such as endophytic fungi kelakai, contain various active secondary metabolites that can inhibit cancer cell proliferation so that they can be part of a more public health-friendly supportive therapy approach.Objective: This study aims to prove the cytotoxic activity of the extract of endophytic fungi in kelakai against MCF-7 and Vero cells.Methods: Isolation, purification, and extraction process of secondary metabolites from the endophytic fungi isolates were carried out in the same manner as our previous research. The ethyl acetate extract of kelakai was obtained by extractive fermentation from pure isolates of the endophytic fungi in kelakai. Extraction was carried out by the fractionation method using the ethyl acetate solvent at a ratio of 1:1. Identification of chemical contents, including tannins, alkaloids, flavonoids, saponins, and steroids/terpenoids, was conducted qualitatively. Cytotoxic activity was tested by the MTT method.Results: From the isolate extraction, 2.4 g of ethyl acetate extract was produced. The identification of chemical contents showed positive results, meaning that the extract did contain tannins, flavonoids, alkaloids, steroids, and saponins. The extract cytotoxicity test against MCF-7 and Vero cells yielded IC50 values of 517.3015 μg/ml and 1,074.9152 μg/ml, respectively. Conclusion: Based on these results, the extract of kelakai was not toxic to Vero cells, but it was toxic to MCF-7 cells. These findings suggest that the kelakai can be the basis for exploring local plants as a source of natural medicine while supporting the conservation of endemic plants to provide safer alternative therapies and improve public health. Keywords: Stenochlaena palustris; Endophytic Fungi; MTT; MCF-7; Vero cell